Caracterización morfológica de hongos fitopatógenos en el cultivo de café (coffea arabica l.) sector los Laureles, cantón La Mana, Cotopaxi 2015 - Pacheco Orellana, Wilson Eduardo (2015)
The present research was made in the Los Laureles sector, with coordinates: latitude: 07° 06' 198" S, longitude: 98° 89' 232" W, and at an altitude of 586 msnm; in the La Maná canton, Cotopaxi province. Since, the main cause for the phytopathogenic fungi presence is by technification lack of the crop coffee. It could determine that the fungus impacts greatly to the coffee production that is the Ojo de gallo (Mycena citricolor). The same one that is presented in the beam in both young and old leaves and fruit. The fungus is presented in injuries round gray or brown coloration, which can cause damage are defoliation, premature death of buds. Also, it causes the fruit drop at different development stages. All, these damages induces a decrease in production.